Experimental study of a tunable perfect flexural wave absorber with a piezoelectric shunted resonator - Li, Xiaopeng; Yu, Ziqi; Lee, Taehwa (Frontiers in Physics, 2022)
Metamaterials and metasurfaces have been widely developed recently for extraordinary acoustic and elastic wave control at a deep subwavelength scale. Perfect wave absorption as an extreme case to totally absorb the impinged waves has gained great attention, whereas most existing designs based on local resonance lack tunabilities, making perfect absorption be observed at a single frequency. To overcome this drawback, in this work, we design and fabricate a tunable inductance-resistance (LR) shunted mechanical resonator via a bonded piezoelectric patch for perfect flexural wave absorption at low frequency. The LR shunted absorber could be reconfigured to a broad frequency range for perfect flexural wave absorption. The tunable perfect absorption performances are validated through experiments and unit absorption is achieved in experiments. In the end, to further highlight the advantages of shunted damping we numerically demonstrate that the absorption spectrum could be enhanced to broadband absorption with a negative capacitance and an inductance-resistance circuit (NC-LR) connected in parallel. The approach proposed provides an alternative solution to achieve perfect wave absorption in the low-frequency range and enables practical application in complex engineering structures.